Influence of Seed Size and Pretreatments on Seed Germination and Seedling Vigour of Pterocarpus Marsupium roxb - Singh, Ved Pal; Kumar, Devendra (Indian Forester, 2014)
Pterocarpus marsupium Roxb. (Bijasal) is an important multipurpose tree species valued for its timber, fuel and fodder. Three experiments were carried out to determine the effect of various seed sizes, time of sowing and pretreatments on seed germination and growth performance in terms of vigour. Higher germination percentage was found during July and August. Larger size seeds > 3.78 mm (T ) (wt. 68.8gm/100 seeds) showed higher seed germination percentage as 3 compared to rest treatments. Root length, shoot length and total dry matter production of seedlings were measured for computing the vigour index. Seeds soaked in cold water for 24h (T ) showed higher germination percentage and 4 significantly higher growth in terms of vigour index. Large sized seed pretreated in cold water for 24h sowed during July and August gave better seed germination and seedlings quality.